Cellular uptake enhancement of Tat-GFP fusion protein loaded in elastic niosomes. - Manosroi A. (2014)
This study has demonstrated the enhancement of cellular uptake of GFP when fused with Tat (Tat-GFP) and loaded in elastic niosomes. GFP and the GFP fused with Tat at C- and N-terminals were expressed in E. coli BL21 (DE3). The N-terminal Tat-GFP fusion protein (Tat-GFP) which showed the highest uptake of 5.2% in HT-29 cell line at 2.4 folds of GFP was selected to load in various charged non-elastic and elastic niosomes and liposomes. All niosomes showed higher entrapment efficiency (EE) of the fusion protein more than in liposomes with the highest EE of 100% in elastic cationic niosomes. However, the fusion protein loaded in elastic anionic niosomes (Tween 61/cholesterol/dicetyl phosphate at 1:1:0.05 molar ratio) which gave the EE of only 32.8% showed the highest cellular uptake of GFP at 6.7, 2.8 and 1.7 times of GFP, Tat-GFP and Tat-GFP loaded in elastic cationic niosomes, respectively. After the 3 month-storage at 30 +/- 2 degrees C, the percentages remaining of the fusion protein loaded in the elastic anionic niosomes (61.9 +/- 12.7%) were about 2 times higher than the non-loaded fusion protein (33.7 +/- 2.8%). Thus, the cellular uptake and the chemical stability of the fusion protein were enhanced when loaded in elastic niosomes, especially the elastic anionic niosomes which can be further developed as an efficient delivery system for many therapeutic proteins.